The Influence of Social Media Influencers and Investment Motivation on Stock Purchase Intention, Moderated by Fear of Missing Out (FOMO), in the Capital Market Among Students of the University of Mataram - Ginanjar Wisnu Alparizi; Didy Ika Supryadi; Abdurrahman (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of social media influencers and investment motivation on stock purchase intention, with Fear of Missing Out (FOMO) as a moderating variable among students of the University of Mataram. The hypotheses proposed are that social media influencers and investment motivation have a positive and significant effect on stock purchase intention, and that FOMO moderates these relationships. This research employs a quantitative approach with a causal associative design. The population consists of 235 students who are members of the Capital Market Study Group (KSPM) at the University of Mataram, with a sample of 100 respondents selected using random sampling techniques. Data were collected through a questionnaire based on a 5-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that social media influencers have a positive and significant effect on stock purchase intention, with an original sample value of 0.518, a T-statistic of 6.214, and a p-value of 0.000. Investment motivation also has a positive and significant effect on stock purchase intention, with an original sample value of 0.389, a T-statistic of 7.677, and a p-value of 0.000. Furthermore, FOMO is found to strengthen the influence of social media influencers on stock purchase intention, with an original sample value of 0.079, a T-statistic of 1.974, and a p-value of 0.048, while it weakens the influence of investment motivation on stock purchase intention, with an original sample value of -0.140, a T-statistic of 2.927, and a p-value of 0.003. The implications of this study highlight the importance of social and psychological factors in shaping investment behavior. Future research is recommended to expand the research scope and include additional variables to obtain more comprehensive results.